Respuesta :

Answer:

[tex](f\circ g)(x)=12x^2+168x+583[/tex]

Step-by-step explanation:

We are given the two functions:

[tex]f(x)=12x^2-5\text{ and } g(x)=x+7[/tex]

And we want to find:

[tex](f\circ g)(x)[/tex]

This is equivalent to:

[tex]=f(g(x))[/tex]

Therefore:

[tex]=f(x+7)[/tex]

Then by substitution:

[tex]=12(x+7)^2-5[/tex]

Square:

[tex]=12(x^2+14x+49)-5[/tex]

Distribute:

[tex]=(12x^2+168x+588)-5[/tex]

Simplify:

[tex]=12x^2+168x+583[/tex]

Therefore:

[tex](f\circ g)(x)=12x^2+168x+583[/tex]

ACCESS MORE